Postpartum Hemorrhagic Morbidity with Scheduled versus Unscheduled Cesarean Delivery at Term - Wiley, Rachel L.; Chauhan, Suneet P.; Johnson, Emily A.; Ghose, Ipsita; Ciomperlik, Hailie N.; Mendez-Figueroa, Hector (American Journal of Perinatology, 2024)
This study aimed to compare the composite maternal hemorrhagic outcomes (CMHOs) among term (≥37 weeks) singletons who had scheduled versus unscheduled cesarean deliveries (CDs). A subgroup analysis was done for those without prior uterine surgeries.Retrospectively, we identified all singletons at term who had CDs. The unscheduled CDs included individuals admitted with a plan for vaginal delivery with at least 1 hour of attempted labor. CMHOs included any of the following: estimated blood loss of ≥1,000 mL, use of uterotonics (excluding prophylactic oxytocin) or Bakri balloon, surgical management of hemorrhage, blood transfusion, hysterectomy, thromboembolism, admission to intensive care unit, or maternal death. Multivariable Poisson regression models with robust error variance were used to estimate adjusted relative risks (aRRs) with 95% confidence intervals (CIs).Of 8,623 deliveries in the study period, 2,691 (31.2%) had CDs at term, with 1,709 (67.3%) scheduled CDs, and 983 (36.5%) unscheduled CDs. Overall, the rate of CMHO was 23.3%, and the rate of blood transfusion was 4.1%. CMHOs were two-fold higher among unscheduled (34.5%) than scheduled CDs (16.9%; aRR = 2.18; 95% CI: 1.81–2.63). The aRRs for blood transfusion and surgical interventions to manage postpartum hemorrhage were three times higher with unscheduled than scheduled CDs. The subgroup analysis indicated that among the cohorts without prior uterine surgery, the rate of the CMHOs was significantly higher when the CD was unscheduled versus scheduled (aRR = 1.85; 95% CI: 1.45–2.37).Compared to scheduled CDs, the composite hemorrhagic adverse outcomes were significantly higher with unscheduled CDs.
Keywords: postpartum hemorrhage; cesarean delivery; transfusion; uterotonics